Supporting and growing privately protected areas in Australia: Interview with The Nature Conservancy's James Fitzsimons. (13th June 2021) - Fitzsimons, James; McDonald, Tein
Abstract : The intent of The Nature Conservancy in Australia has always been to optimise conservation outcomes for people and nature, partnering with government, Indigenous and private landowners through a range of initiatives. James Fitzsimons chronicles some of the organisation's projects and reveals some of its secrets to success.